COMPOUND WORDS FOUND IN THE REPUBLIKA NEWS ARTICLE - Asti siti Nurazizah; venna syifaa Nurnazhafah (PROJECT (Professional Journal of English Education), 2018)
This study aimed to analyze English compound words in Republika news article. The purpose of research is finding the forms of compound words and the meaning of compound words found in Republika news article. To achieve the objectives, the writers use descriptive qualitative as the type of the research. The data are in form of compound words, in collecting the data the writers use documentation technique and the steps are reading the article, selecting and collecting the data systematically in accordance with the forms and the meaning of compound words. Based on the data analysis the writers found 11 data of compound words in Republika news article. There are three forms of compound words, they are Noun compound (7 data), Verb compound (3 data), and Adjective compound (1 data). And the meaning of compound words, there are 7 data which belong to transparent meaning and there are 4 data which belong to opaque meaning.